A Biomechanical Analysis of Weighted Lifting With an Active Knee Exoskeleton - Margaret A. Meagher; Grace R. Hunt; Brendon Ortolano; Rosemarie Murray; Lukas Gabert; Kenneth Bo Foreman; Tommaso Lenzi (IEEE Access, 2025)
Manual material handlers experience some of the highest injury rates among professions monitored by the Bureau of Labor Statistics. Most of these injuries are musculoskeletal strains, sprains, and tears linked to repeated lifting and lowering of heavy objects. Powered exoskeletons may help to lessen the strain on the musculoskeletal system during lifting. Previous studies have indicated that powered knee exoskeletons can reduce muscle activation and metabolic cost while lifting. However, no prior studies have conducted comprehensive biomechanical analyses using motion capture during exoskeleton-assisted lifting, which is crucial for examining joint-level effects of the assistance. In this study, we employed a bilateral powered knee exoskeleton to assist eight healthy subjects as they repeatedly lifted and lowered a 9 kg box. We utilized electromyography sensors to record quadriceps muscle activity and full-body motion capture to evaluate angles, torques, and positions of the lower limb joints. The exoskeleton decreased the peak electromyography activations of four quadriceps muscles — the right and left vastus medialis and vastus lateralis – with three reductions being statistically significant (29.2%, 31.2%, and 30.9% reduction compared to lifting without the exoskeleton, p <0.05). Additionally, we observed significant decreases in biological knee torque with the exoskeleton (53.4% and 53.58% reduction compared to lifting without the exoskeleton, p <0.05). These findings suggest that powered knee exoskeletons could serve as an effective tool for reducing effort during occupational lifting, potentially lowering the risk of injury among manual material handlers by encouraging a safer, knee-centric lifting form.